Selectfluor-Mediated Oxidative Dehydrogenation of Hydrazines: A Process for the Synthesis of Azo Compounds - Zhao, Yulei; Li, Shuai; Cui, Jinjie; Wang, Huimin; Kang, Xin; Wang, Yan; Tian, Laijin (Synthesis, 2022)
A facile method to synthesize azo compounds from hydrazine derivatives is developed. This represents the unprecedented example of Selectfluor-mediated oxidative dehydrogenation of hydrazine derivatives. The reaction might proceed through N-fluorination and elimination processes. This protocol exhibits key features including simple operation, mild conditions, good functional group tolerance, and high efficiency. Moreover, the advantage is also highlighted by the conversion of a sulfonyl-substituted azo compound to furnish acetanilide in excellent yield under 4 W blue LED irradiation.
Keywords: oxidation; dehydrogenation; azo compounds; hydrazines; Selectfluor